Patterns of SAC Utilization and the Sine Qua Non of the Self-Propelled Development of StudentsÃ¢â¬â¢ English Proficiency - Furaidah ; Suharmanto (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
This article reports on a study intended to find out the patterns of the Self Access Center (SAC) utilization by students ofÃÂ  the English Departments, State University of Malang, and toÃÂ  explore the most effective pattern in developing students English proficiency as well as students learning autonomy. The study involved 207 students of various years. The data were collected through questionnaires, observations, and interviews. Analyses of the students responses to the questionnaires resulted in the findings that the more advanced the students were, the less frequently they utilized the SAC; that the students proficiency was improving along with classes; and that the students were autonomous in their learning. In addition, the study also found out that the materials and activities need to be periodically updated in order for the SAC ÃÂ to better serve the learning needs of the more advanced students.ÃÂ